Do the etiology of hyponatremia and serum sodium levels affect the length of hospital stay in geriatric patients with hyponatremia? - Baser Salih; Yılmaz Cakmak Nuray; Gemcioglu Emin (Journal of Medical Biochemistry, 2022)
Background: Hyponatremia can lead to a prolonged hospital stay and increased morbidity and mortality rates in geriatric patients. This study aimed to evaluate the effects of hyponatremia etiology and serum sodium (Na) levels on hospitalisation time in geriatric patients hospitalised due to hyponatremia. Methods: The demographic characteristics, laboratory data, etiology of hyponatremia, and length of hospital stay were retrospectively recorded for 132 patients over 65 years of age who were hospitalised for hyponatremia. Results: Of the 132 patients, 90 were female (68.2%), and 42 were male (31.8%). The serum Na levels of 66 (50%) patients were <120 mmol/L, those of 64 (48.5%) patients were 120-129 mmol/L, and those of two (1.5%) patients were >130 mmol/L. One hundred nine (82.6%) patients had hypoosmolar hyponatremia, 14 (10.6%) patients had isoosmolar hyponatremia, and nine (6.8%) patients had hyperosmolar hyponatremia. Also, 19.7% of the patients were hypovolemic, 37.9% were euvolemic, and 42.4% were hypervolemic. Hyponatremia etiology was congestive heart failure in 38 (28.8%) patients, syndrome of inappropriate antidiuretic hormone in 29 (22.0%) patients, gastrointestinal fluid loss in 24 (18.2%) patients, renal pathologies in 20 (15.2%) patients, the presence of drugs in 20 (15.2%) patients, and hypocortisolemia in one (0.8%) patient. The mean length of hospital stay for the patients was five (1-60) days. There was no statistically significant difference between the lengths of hospital stay based on hyponatremia etiology and serum Na levels (p=0.861 and p=0.076). It was observed that the lengths of stay for patients who developed hyponatremia during their hospitalisation in various clinics were longer than those for patients who presented to the emergency department (p<0.001). Conclusions: In this study, it was determined that the length of hospital stay did not change with the etiology of hyponatremia and serum Na level at the time of admission, but patients who developed hyponatremia during their hospitalisation had longer hospitalisation times.